2017
DOI: 10.1002/jcla.22277
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of pretreatment inflammatory biomarkers as independent prognostic indicators in prostate cancer

Abstract: The pretreatment NLR and PLR might be beneficial to predict the progression and prognosis of PCa. Furthermore, NLR was more effective than PLR acting as an independent prognostic indicator for PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
5
23
0
Order By: Relevance
“…At last, 6 articles published between 2015 and 2017 were included for meta-analysis. Three studies were performed in China, [ 14 , 16 , 18 ] one was conducted in Spain, [ 15 ] one in Italy, [ 17 ] and one in Austria. [ 19 ] All 6 studies reported data on overall survival (OS) and 4 studies showed data on disease-free survival (DFS).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At last, 6 articles published between 2015 and 2017 were included for meta-analysis. Three studies were performed in China, [ 14 , 16 , 18 ] one was conducted in Spain, [ 15 ] one in Italy, [ 17 ] and one in Austria. [ 19 ] All 6 studies reported data on overall survival (OS) and 4 studies showed data on disease-free survival (DFS).…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] All 6 studies reported data on overall survival (OS) and 4 studies showed data on disease-free survival (DFS). [ 14 16 , 19 ] The cut-off values of PLR ranged from 117.58 to 210. All studies had a retrospective study design and a Newcastle–Ottawa scale (NOS) score ≥6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RDW is a parameter that reflects the heterogeneity of peripheral red blood cell volume and is considered to be a systemic inflammatory marker of in many chronic inflammation . As a low‐cost test, it is usually reported in the complete blood counts .…”
Section: Discussionmentioning
confidence: 99%